3 - Social Scientists’ Failure of Analytical Nerve: ‘Africa Rising’ from Above, or Uprising from Below? - Bond, Patrick (Africa Development, 2021)
If Africa has been ‘rising’ since the outset of early 2000s commodity super- cycle, as so many of its elites and allied international economic actors claim, what are we to make of the evidence of growing popular uprisings? This survey of narratives and evidence finds convincing the converse claim that ‘rising’ translates into ‘crashing’ when a more accurate accounting is made of the continent’s wealth. As a result of systematic looting, around 2010 the continent’s most advanced social movements began awakening from the apparent 2000s slumber, in the wake of an earlier era of IMF Riots dating to the 1980s. At that stage, the intensity of rhetoric between the contending forces grew shrill, and some such conflicts were resolved only by recourse to state force. This is the point at which the failure of the progressive African intelligentsia’s nerve was most acute: in its failure to either validate the merits of export-led growth based on extractive industries, as conventional wisdom had it but against which was all prior evidence and deep empirical observation, or to promote resistance by civil (and often uncivil) society. Will African social scientists return to some of the ideals that forty years ago helped make the continent one of the world’s richest sources of revolutionary thought? Or instead, do the dialectics of wealth generation and socia upheaval call forth no more than intellectual disinterest or, indeed, fear?